Charakterystyka hydrologiczna Jeziora Trześniowskiego i Jeziora Łagowskiego (woj. lubuskie) = Hydrological characteristics of Trzesniowskie and Lagowskie lakes (Lubuskie province) - Ogiołda, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Trzesniowskie and Łagowskie lakes are localised in Łagów in lubuskie province. They are situated in the same post-glacial gully, their parameters are typical for such lakes. Water quality is better for Trzesniowskie, but both are getting better during last twenty years.
Keywords: hydrologia; opady; parametry morfometryczne; jakość wód gruntowych; hydrology; precipitation; morfometric parameters; water quality